EFEKTIVITAS PERMAINAN ENGKLEK UNTUK MENGENAL BILANGAN BAGI ANAK TUNAGRAHITA SEDANG X DIII C1 SLB C PAYAKUMBUH (Single Subject Research) - Siska Permata Sari (Jurnal Penelitian Pendidikan Khusus, 2015)
Abstract: This study was motivated by the problems that researchers have found in SLB C Payakumbuh, a retarded child were sitting in class DIII / C1 are not familiar with numbers. This type of research is experimental approach in the form of Single Subject Research (SSR) with ABA design. baseline conditions before being given a treatment of data collected using the data collection tool the ability to know numbers 1-10 that is by counting the number of numbers mentioned ditujuk and children show the percentage of 10%. the intervention condition when given treatment with hopscotch game the ability to know numbers can be mentioned the child shows the percentage of 100% .. then on baselineII condition after being given treatment using child hopscotch game could mention numbers without the aid shows the percentage of 80% .. Data were analyzed with using visual data analysis is illustrated through a graph. Analysis of the data showed an increased ability to recognize numbers through a hopscotch game in which this game in every box is numbered. Based on data analysis that has been done, it can be concluded that through the hopscotch game can improve the ability to know the number of children with intellectual challenges being X. Kata kunci: Mengenal bilangan 1 sampai 10 :permainan engklel :tunagrahita sedang